Self-Optimization of Low Coverage and High Interference in Real 3G/4G Radio Access Networks - Sousa, Marco (2018)
This paper presents a new single cell multi-objectiveoptimization algorithm. The objective is to optimize areas oflow coverage and high interference simultaneously, through theadjustment of the antenna tilts and/or antenna orientation. Theprocess is achieved using a specific implementation of a ParticleSwarm Optimization (PSO) algorithm. Both the detection ofsub-optimal performance areas and its subsequent optimizationare supported by Drive Test (DT) data and network topologyinformation. The antenna optimization algorithm was tested withreal data in 3rd Generation (3G)/4th Generation (4G) networks.In this work, a 3G urban scenario is highlighted, achieving anaverage optimization gain of 78%.